Comparison of effectiveness of transsternal and thoracoscopic thymectomy in the treatment of myasthenia gravis - Gątarek, Juliusz; Orłowski, Tadeusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Aim: The aim of the study was to compare effectiveness of transsternal and thoracoscopic thymectomy in the treatment of myasthenia gravis. Material and methods : Between May 2002 and May 2005, a randomised prospective trial was performed. The trial included 50 myasthenia gravis patients treated by thymectomy. 28 patients underwent right side extended thoracoscopic thymectomy with neck incision and 22 patients – extended transsternal thymectomy. The results of these two methods were compared using statistical methods. The Myasthenia Gravis Foundation of America classifications were used to assess pre-operation disease severity and results of surgical treatment. Results: There were 36 (72%) women and 14 (28%) men included in the study. Mean age was 33 years (range from 16 to 71). Mean follow up was 9.3 months (range from 1 to 36). There was 24% (12 patients) postoperative morbidity and no mortality. There was no significant difference in both groups regarding postoperative morbidity. In the sternotomy group there was 95% (21 patients) improvement rate and none of the patients achieved complete stable remission. In the thoracoscopy group there was 64% (18 patients) improvement rate and 4% (1 patient) complete stable remission rate. The rate of positive results (complete stable remission or improvement) was higher in the sternotomy group and the difference was statistically significant (p = 0.029). Conclusions : Although the study showed better results after transsternal thymectomy, a short period of follow up does not allow for definitive assessment of the methods being compared. A limited time of follow up and very strict criteria of the postintervention status evaluation recommended by MGFA and used in this trial seem to be the main reason for the low complete stable remission rate obtained in the presented series.